2010
DOI: 10.1007/s11102-010-0286-8
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly as a cause of 1,25-dihydroxyvitamin D-dependent hypercalcemia: case reports and review of the literature

Abstract: Growth hormone excess has been associated with hypercalciuria and nephrolithiasis. Hypercalcemia in acromegaly is rare and usually due to coexistent primary hyperparathyroidism. To report two cases of 1,25-dihydroxyvitamin D (1,25 (OH)(2) D)-dependent hypercalcemia in cromegaly. A 50 year-old female with 2 years history of hypercalcemia presented with features of acromegaly. Serum calcium (Ca) was 10.9 mg/dl (8.6-10.2), parathyroid hormone (PTH) 20 pg/ml (10-65), PTH-related peptide undetectable, and 1,25 (OH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 31 publications
1
19
0
3
Order By: Relevance
“…High calcium level with normal PTH has been described in two acromegalic patients in whom the hypercalcemia was 1,25(OH)2D dependent (31). Whether excess GH or IGF1 increases the production of 1,25(OH)2D in humans remains to be elucidated.…”
Section: Discussionmentioning
confidence: 95%
“…High calcium level with normal PTH has been described in two acromegalic patients in whom the hypercalcemia was 1,25(OH)2D dependent (31). Whether excess GH or IGF1 increases the production of 1,25(OH)2D in humans remains to be elucidated.…”
Section: Discussionmentioning
confidence: 95%
“…The etiology of hypercalcemia includes primary hyperparathyroidism (2, 4) or 1,25-dihydroxy-vitamin D [1,25(OH) 2 D] excess (5,6). Studies in patients treated for acromegaly have reported that posttreatment mean parathyroid hormone (PTH) levels were unchanged (2) or higher compared with baseline (7,8).…”
mentioning
confidence: 99%
“…While hypercalcemia in the setting of acromegaly is most often due to coexisting primary hyperparathyroidism, these case reports document that complete tumor resection resulted in resolution of 1,25(OH) 2 D-mediated hypercalcemia in two of three patients. 86,87 In one patient with residual tumor, the hypercalcemia did not resolve and 1,25(OH) 2 D concentrations remained elevated. 86 While the mechanism of 1,25(OH) 2 Dmediated hypercalcemia is not fully elucidated in patients with acromegaly, IGF-I has been reported as a stimulator of 1,25(OH) 2 D production in animal studies.…”
Section: 25(oh) 2 D-mediated Hypercalcemia Via Renal 1α-hydroxylasementioning
confidence: 93%
“…86,87 In one patient with residual tumor, the hypercalcemia did not resolve and 1,25(OH) 2 D concentrations remained elevated. 86 While the mechanism of 1,25(OH) 2 Dmediated hypercalcemia is not fully elucidated in patients with acromegaly, IGF-I has been reported as a stimulator of 1,25(OH) 2 D production in animal studies. 88,89…”
Section: 25(oh) 2 D-mediated Hypercalcemia Via Renal 1α-hydroxylasementioning
confidence: 93%